Penerapan Pendampingan Kompetisi Sains Nasional Bidang Ekonomi dalam Upaya Meningkatkan Kompetisi Siswa SMAN 1 Prambanan Untuk Menghadapi KSN Bidang Ekonomi - Rahmawati, Nur; Almuntaha, Eska; Emiliana, Maria; Revania, Nadya; Septi, Anggun (LPPM IST AKPRIND Yogyakarta, 2024)
The National Science Competition (KSN) in Economics is a national scale event that talented and outstanding high school students throughout Indonesia attend. KSN activities are an annual agenda of the Ministry of Education, Culture, Research and Technology which is an opportunity for all students to show their best abilities in science and technology. Competition among students is getting tighter, the breadth and depth of material also requires students to study hard, not just from textbooks. To increase students' competence in dealing with KSN in the Economic Sector, the Community Service Team (PkM) of the Digital Business Study Program at AKPRIND University provides assistance and training to students at SMAN 1 Prambanan, Sleman, Special Region of Yogyakarta using sharing, discussion and question and answer methods. Through an integrated, harmonious, and synergistic approach, this activity involves internal and external stakeholders. The method of mentoring, guidance, refreshment material, and training to answer KSN Economics questions is practiced by a team of lecturers who have areas of expertise in the material presented. Evaluation of activities shows positive responses from students and success in improving their ability to understand Economics material and preparing themselves to face national-level competitions. The PkM implementation model has proven to be effective and needs to be continued, while future improvements can be focused on increasing cooperation between related parties and optimizing study time.